Modern Beijing sublineage of Mycobacterium tuberculosis shift macrophage into a hyperinflammatory status. Issue 1 (31st December 2022) - Tong, Jingfeng; Meng, Lu; Bei, Cheng; Liu, Qingyun; Wang, Min; Yang, TingTing; Takiff, Howard E.; Zhang, Shuye; Gao, Qian; Wang, Chuan; Yan, Bo
ABSTRACT: The high prevalence of the modern Beijing sublineage of Mycobacterium tuberculosis may be related to increased virulence, although the responsible mechanisms remain poorly understood. We previously described enhanced triacylglycerol accumulation in modern Beijing strains. Here we show that modern Beijing strains grow faster in vitro and trigger a vigorous immune response and pronounced macrophage infiltration. Transcriptomic analysis of bone marrow derived macrophages infected with modern Beijing lineage strains revealed a significant enrichment of infection, cholesterol homeostasis and amino acid metabolic pathways. The upregulation of proinflammatory / bactericidal cytokines was confirmed by RT–PCR analysis, which is also in consistent with the reduced bacterial burden in modern strains infected macrophages. These results suggest that modern Beijing strains elicit a hyperinflammatory response which might indicate a stronger virulence and contribute to their extensive global prevalence.